THE CONCEPT OF PHYSICAL EDUCATION: A VISION OF BEGINNING STUDENTS AND GRADUATING STUDENTS OF THE COURSE OF PHYSICAL EDUCATION, UNIVERSITY FEDERAL DE MATO GROSSO, MATO GROSSO STATE, BRAZIL (Fiep Bulletin - online, 2011)
Physical Education had its concept reviewed by Manifest World of Physical Education - FIEP 2000, which extends its definition of infancy and adolescence, to be a Physical Education for children, adolescents, young, adults and the elderly, becoming a school for the acquisition of motor ability, attitudes and knowledge. Thus, this study verified the conceptual construction of Physical Education of students beginners (2008 and 2009) and students who are completing the Course of Physical Education (2009) of Federal University of Mato Grosso. Was asked for students to finalize the phrase: Physical Education is ...? This was supplemented by 67 academics, including 54 students beginning at and 13 graduates between 17 and 40 years. Note that yet there isn't a structured concept of physical education. It is noticeable that when starting the University, only some content (usually sports) are taken as content of Physical Education. Physical education is not understood as a discipline that uses pedagogically, the knowledge of an area known as body culture, which together with themes and forms of activities such as play, sports, gymnastics, dance or other constituting its content. Currently, Physical Education isn't a matter only of students, it is also characterized by a set of activities performed by individuals through natural movement and everyday, exercised in a rational, methodical and progressive form, aimed at developing the physical qualities, intellectual, moral, social, psychological and physiological of the practitioner. Considering these aspects, Physical Education may, in fact, be considered the area that studies and acts on the body culture movement.
Keywords: body culture; conceptual construction; themes and content of Physical Education